Hubungan Kesejahteraan Spiritual dengan Kualitas Hidup pada Pasien Kanker Payudara di Poli Bedah RSUP Dr. M. Djamil Padang - Lola Despitasari; Lenni Sastra; Fitria Alisa; Letivia Azro (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2020)
Di Indonesia peningkatan jumlah kasus baru serta jumlah kematian akibat kanker payudara terus meningkat. Situasi yang dialami pasien kanker payudara menyebabkan permasalahan meliputi perubahan secara fisik, fungsi sosial, psikis maupun spiritual seseorang dan ini mempengaruhi kualitas hidup pasien kanker payudara. Salah satu faktor yang mempengaruhi kualitas hidup pasien kanker payudara adalah kesejahteraan spiritual. Tujuan penelitian untuk mengetahui hubungan kesejahteraan spiritual dengan kualitas hidup pada pasien kanker payudara di Poli Bedah RSUP Dr. M. Djamil Padang. Jenis penelitian analitik dengan desain cross sectional. Populasi pada semua wanita penderita kanker payudara yang datang ke poli bedah RSUP Dr.M.Djamil Padang sebanyak 509 orang dengan jumlah sampel sebanyak 83 orang.Teknik pengambilan sampel dengan accidental sampling. Data di analisa menggunakan uji Chi square. Hasil penelitian 44,6% pasien kanker payudara memiliki kualitas hidup buruk, 53% memiliki kesejahteraan spiritual yang buruk. Hasil uji statistik didapatkan p value 0,000(p ≤ 0,05), terdapat hubungan antara kesejahteraan spiritual dengan kualitas hidup pada pasien kanker payudara di Poli Bedah RSUP Dr.M.Djamil Padang. Disimpulkan bahwa pasien kanker payudara dengan kesejahteraan spiritual buruk cenderung memiliki kualitas hidup buruk. Diharapkan kepada tenaga kesehatan melakukan penyuluhan dan informasi yang edukatif tentang kualitas hidup kanker payudara sehingga meningkatkan kesejahteraan spiritual.Kata kunci : kanker payudara; kualitas hidup; kesejahteraan spiritual THE RELATIONSHIP OF SPIRITUAL WELFARE WITH QUALITY OF LIFE IN BREAST CANCER PATIENTS IN SURGERY POLYCLINIC AT Dr. M. DJAMIL PROVINCIAL GENERAL HOSPITAL OF PADANG ABSTRACTIn Indonesia the increase of new cases and the number of deaths from breast cancer continues to increase. The situation experienced by breast cancer patients cause problems include physical changes, social functions, psychic and spiritual of someone. The impact of these problems will affect the quality of life of breast cancer patients. One of the factors that affect the quality of life of breast cancer patients is spiritual welfare. The purpose of this study was to determine the relationship of spiritual welfare with quality of life in breast cancer patients in Surgery Policlinic at Dr. M. Djamil Provincial General Hospital of Padang. The type of research used was analytic survey, cross sectional study design. The population in this study were all women with breast cancer who came through surgery polyclinic at Dr. M. Djamil Provincial General Hospital of Padang as many as 509 people with samples were 83 people taken by accidental sampling technique. Univaria data were analyzed using frequency table and bivariate used Chi square. The results showed almost half 44.6%, of breast cancer patients had poor quality of life, more than half 53%, had poor spiritual welfare. Statistical test results obtained p value 0,000 (p ≤ 0.05) means there is a relationship between spiritual welfare with quality of life in breast cancer patients at surgery polyclinic at Dr. M. Djamil Provincial General Hospital of Padang.The results of this study can be concluded that breast cancer patients with poor spiritual welfare have poor quality of life, while breast cancer patients with spiritual well-being have good quality of life. It is expected that health workers to educate and educational information about the quality of life of breast cancer.Keywords : breast cance; quality of life; spiritual welfare